Distribution and Risk Assessment of Metals in Surface Water and Sediment in the Upper Reaches of the Yellow River, China. Issue 8 (16th November 2016) - Zuo, Hang; Ma, Xiaoling; Yang, Kai; Chen, Yizhen; Chen, Jianhua; Guo, Yang; Zhao, Jiaying; Wang, Ruming; Fang, Fang; Liu, Ying
ABSTRACT: In order to study the metal pollution in the upper reaches of the Yellow River, samples were collected from 12 selected sites along the river, in Gansu, Ningxia and Inner Mongolia, in October 2014. The concentrations of Aluminum (Al), Arsenic (As), Barium (Ba), Beryllium (Be), Cadmium (Cd), Chromium (Cr), Copper (Cu), Lead (Pb), Mercury (Hg), Manganese (Mn), Nickel (Ni), Strontium (Sr), Thallium (Tl), Vanadium (V) and Zinc (Zn) in surface water and sediment samples were determined, using inductively coupled plasma mass spectrometry (ICP-MS) and atomic fluorescence spectrometry (AFS). Compared with water quality standards from China, the US EPA and WHO, Al, Cr, Cd, Mn and Pb were recognized as water pollutants. As, Be, Cd, Cr, Cu, Ni and V exceeded the local background values in soil. Ecological risk assessment of sediments showed that most sampling sites lay in the level of middle to high risk and that Cd, with a high, increased the potential ecological risk index in every sampling site. The parameters for human health risk assessment—the Hazard Quotient ( HQ ingestion, HQ dermal ) and the Hazard Index ( HI )—demonstrated that As and Tl were the most important pollutants in this area, and that oral intake was the main exposure pathway.